Impact of Corporate Social Responsibility on Consumer Trust in Nepalese Commercial Banks - Chand, Srijana (Nepalese Journal of Economics, 2024)
This study examines the impact of corporate social responsibility (CRS) on consumer trust in Nepalese commercial banks. Customer trust is the dependent variable. The selected independent variables are service quality, organization identification, employee commitment, organization attractiveness, and organization morality. The primary source of data is used to assess the opinions of the respondents regarding the perception of service quality, organization identification, employee commitment, organization attractiveness, and organization morality. The study is based on primary data of 20 commercial banks with 125 respondents. To achieve the purpose of the study, structured questionnaire is designed. The regression models are estimated to test the significance and importance of impact of corporate social responsibility on consumer trust in Nepalese commercial banks.The result showed that service quality has a positive impact on consumer trust. It implies that better the service quality, better would be the customer trust. Similarly, organization identification has a positive impact on customer trust. It indicates that specific organization identification leads to increase customer trust. Likewise, employee commitment has a positive impact on customer trust. It indicates that the influence of committed employee drives positive impact on customer trust. Further, organization attractiveness has a positive impact on customer trust. It indicates that organization attractiveness stimulates the positive customer trust. Moreover, the result also shows that organization morality has a positive impact on customer trust. It indicates that higher the organization morality, higher would be the customer trust.